People's republic - Muchamore, Robert (London : Hodder Children's Books, 2006)
Twelve-year-old Ryan is CHERUB's newest recruit. He's got his first mission: infiltrating the billion-dollar Aramov criminal empire. But he's got got no idea that this routine job will lead him into an explosive adventure involving drug smugglers, illegal immigrants and human trafficking, or that his first mission will turn into one of the biggest in CHERUB's history.
Keywords: Mystery -- Fiction -- Adventure; Young Adult -- Thriller